Kekuatan Batas Lambung Kapal dalam Menahan Momen Lentur Vertikal - Azhar Aras Mubarak; Ganding Sitepu; Muhammad Zubair Muis Alie (Jurnal Penelitian Enjiniring, 2018)
On the life, the ship will constantly get the structural load caused by the external load of the internal waves and loads of the ship's load and the structure itself which then reaches the ultimate strength of the structure. This study aims to determine the strength of the boundary of the hull due to the vertical bending moment so that the ship structure can be guaranteed security. The analysis was done by using finite element method (FEM) by modeling the structure of the tanker section modified based on the shape of the girder box so that a simpler model is obtained. This calculation is done by using ANSYS 17 software. The calculation of vessel structure is simulated based on two existing models namely girder box model and modified tanker model. In the girder box model, ultimate strength is obtained at 6,311 x 108 Nmm for hogging conditions and -6.311 x 108 Nmm for sagging conditions. While on the tanker model, the ultimate strength obtained is -8.99 x 1012 Nmm for sagging conditions and 1.0277 x 1013 Nmm for hogging conditions.